2021
DOI: 10.1094/pdis-06-20-1361-re
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies for Fusarium Head Blight Resistance and Its Trade-Off With Grain Yield in Soft Red Winter Wheat

Abstract: Identification of quantitative trait loci for Fusarium head blight (FHB) resistance from different sources and pyramiding them into cultivars could provide effective protection against FHB. The objective of this study was to characterize a soft red winter wheat (SRWW) breeding population that has been subjected to intense germplasm introduction and alien introgression for FHB resistance in the past. The population was evaluated under misted FHB nurseries inoculated with Fusarium graminearum infested corn spawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
38
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 59 publications
8
38
1
Order By: Relevance
“…Among them, one QTL for FDK was mapped between 611 and 724 Mbp in the ‘Nanda 2419 × Wangshuibai’ population ( Li et al, 2008 ). Additionally, a recent GWAS using soft red winter wheat germplasm reported a QTL for type III and type IV resistance that was mapped at 738 Mbp, which perfectly co-localizes with the MTA from current study ( Gaire et al, 2021 ). Previously, Larkin et al (2020) also reported a QTL for type II resistance at 709 Mbp on chromosome 7A, which is in close proximity to the MTA S7A_713432647 from this study.…”
Section: Discussionsupporting
confidence: 76%
“…Among them, one QTL for FDK was mapped between 611 and 724 Mbp in the ‘Nanda 2419 × Wangshuibai’ population ( Li et al, 2008 ). Additionally, a recent GWAS using soft red winter wheat germplasm reported a QTL for type III and type IV resistance that was mapped at 738 Mbp, which perfectly co-localizes with the MTA from current study ( Gaire et al, 2021 ). Previously, Larkin et al (2020) also reported a QTL for type II resistance at 709 Mbp on chromosome 7A, which is in close proximity to the MTA S7A_713432647 from this study.…”
Section: Discussionsupporting
confidence: 76%
“…VIBE was the only platform to effectively detect a significant SNP association within the Fhb1 region [−log 10 (p) of 5.53, S3B_9439629 locus] (Figure 6). While significant SNP associations of other major FHB QTL (F1BJ, F1AN) shown to be present in this population were not detected by VIBE or other platforms, both F1BJ and F1AN were previously detected using DON as a phenotype, rather than FDK as was used to detect Fhb1 [4,16,23]. VIBE proved to be the most effective proxy phenotype to DON among platforms (Figure 4), but still failed to associate with QTL previously detected in GWAS using DON, such as F1BJ and F1AN (Figure 5).…”
mentioning
confidence: 88%
“…Consequently, FDK bears a closer relationship with DON content in the physiologically mature grain and has a direct effect on test weight as FDK weigh less than healthy kernels [12,15]. For these reasons, DON and FDK are considered primary traits for their direct effect on yield, quality, and ultimate economic value of the grain, compared to FHB incidence and severity which are considered secondary traits [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations